2014
DOI: 10.3325/cmj.2014.55.628
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory effect of sevoflurane in open lung surgery with one-lung ventilation

Abstract: AimTo prospectively assess the antiinflammatory effect of volatile anesthetic sevoflurane in patients undergoing open lung surgery with one lung ventilation (OLV).MethodsThis prospective, randomized study included 40 patients undergoing thoracic surgery with OLV (NCT02188407). The patients were randomly allocated into two equal groups that received either propofol or sevoflurane. Four patients were excluded from the study because after surgery they received blood transfusion or non-steroid antiinflammatory dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 27 publications
0
39
0
3
Order By: Relevance
“…These inflammatory mediators were released in the blood through the pulmonary circulation, and caused multiple organ dysfunction or failure. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory mediators were released in the blood through the pulmonary circulation, and caused multiple organ dysfunction or failure. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…During tube application, the lung is in a collapsed state. Although it is beneficial for surgical operation, OLV can cause lung collapse, which in turn leads to increased intrahepatic shunt, hypoxia and high airway pressure in the healthy lung, causing different degrees of lung injury later ( 16 , 17 ). In this study, the controlled lung collapse based on the previous study on lung injury was proposed for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical researches have investigated the pulmonary inflammatory-modulating effects of sevoflurane and propofol during OLV. Their results suggested that sevoflurane suppressed the local alveolar inflammatory responses and reduced inflammatory mediators release in patients undergoing OLV, resulting in better clinical outcomes in thoracic surgery [ 13 , 21 , 22 ]. A recent meta-analysis by Sun et al also showed that inhalational anesthetics might be preferable for OLV during thoracic anesthesia due to their protective effects of attenuating inflammatory responses when compared with propofol-based intravenous anesthesia [ 23 ].…”
Section: Discussionmentioning
confidence: 99%